Lean construction, BIM, realidad virtual y realidad aumentada para la toma de decisiones en proyectos de infraestructura moderna y patrimonial - Calderón Hernández, Claudia Fabiola (2019)
The technology developed in the last years benefits several industries while improving margins and indicators. This is the case of the BIM tool, virtual reality (VR) and augmented reality (AR). In the construction industry, project managers are more reluctant to using these new technologies, wasting the opportunities of improvement they give. The use of BIM in construction projects has been boosted in the last years, obtaining very good results by integrating it to the Lean Construction philosophy. However, the implementation of visualization tools like VR and AR it’s still on the first phase of research. On this thesis, the state of the art of virtual reality, augmented reality and its application on the construction industry is reviewed and determined. From there, a case study on the design phase of a heritage structure project is done, to evaluate and validate its use during the design phase. In a similar way, it is applied to a concrete building project during the construction phase. Finally, the results obtained are measured comparing them through surveys performed on the project team. The results indicate that even though there is not an automated process to model a heritage infrastructure on BIM, its use on these types of structures has great potential to improve the conservation strategies. Likewise, there is a great compatibility between the management of heritage structures and the Lean Construction philosophy, and the use of its tools, as well as the VR technology promotes an improvement during the design phase, allowing the decision-making process to be more transparent and efficient. As for the building projects, the results validate the methodology of VR/AR implementation in a construction project. The use of VR/AR improves communication within the project team and reduces the time needed for the comprehension of the project documentation and the decision-making process.